Supramolecular Association via Hg···S Secondary-Bonding Interactions in Crystals of Organomercury(II) Species: A Survey of the Cambridge Structure Database - Tiekink, Edward R. T. * (MDPI, 2023)
The Cambridge Structural Database has been surveyed for crystals featuring organo-Hg···S secondary-bonding interactions within supramolecular aggregates. Nearly 50% of crystals where Hg···S interactions could potentially form, featured Hg···S contacts within zero- or one-dimensional supramolecular assemblies with only a few examples of two-dimensional arrays featuring Hg···S interactions. This high propensity of Hg···S contact formation reflects the inherent thiophilic nature of mercury but also the relatively open access to mercury owing to the linear C–Hg–S coordination geometries, the prevalence of close intramolecular Hg···S, Hg···O and Hg···N interactions notwithstanding.